2006
DOI: 10.1111/j.1445-5994.2006.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing attitudes to the management of ischaemic stroke between 1997 and 2004: a survey of New Zealand physicians

Abstract: Aim: In 1997, a survey of New Zealand physicians' opinions on the management of stroke was carried out. Since then, there have been a number of advances in stroke therapy. We have repeated the 1997 survey to assess changes in physicians' opinions on stroke management.Methods: A questionnaire was sent to 293 physicians responsible for patients admitted with acute stroke to hospitals throughout New Zealand. It included questions on the management of acute stroke and secondary prevention and was based on the 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Knowledge about tPA in the management of AIS at the emergency department was poor, average, and good in 54(36%), 55 (36.7%), and 41 (27.3%) individuals, respectively. However, there was no significant difference in overall knowledge based on age; nevertheless, good and average knowledge levels were considerably higher among females, level 3 and level 4 of training, and years of experience 5-10 years (P value 0.05); a similar result was reported by Brown et al [17].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Knowledge about tPA in the management of AIS at the emergency department was poor, average, and good in 54(36%), 55 (36.7%), and 41 (27.3%) individuals, respectively. However, there was no significant difference in overall knowledge based on age; nevertheless, good and average knowledge levels were considerably higher among females, level 3 and level 4 of training, and years of experience 5-10 years (P value 0.05); a similar result was reported by Brown et al [17].…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies suggest emergency physicians are resistant to the use of tPA in stroke [17,18]. A 2005 survey of members of the American College of Emergency Physicians found that even in the ideal setting (defined as CT scanner availability, neuroradiology and neurology support, administrative support, appropriate candidate, etc), 40% of respondents were either "unlikely" or "uncertain" to use tPA [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter survey was limited to emergency physicians from community hospitals participating in a cluster randomised controlled trial [ 11 ]. A 2004 New Zealand (NZ) survey indicated 73% of physicians rarely or never administer tPA treatment [ 12 ]. This sample included a range of health-care providers, limiting the generalisability of findings to the emergency context.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the most important factor resulting in delay in reaching hospital in golden period is the lack of pain in stroke. Attitude of medical professionals toward stroke is equally appalling, a sentiment echoed by stroke specialists worldover [16]. It is not unusual for physicians to admit cases of stroke to general medical ward rather than an intensive care unit, as the patient's general condition is seemingly stable.…”
mentioning
confidence: 99%